Transorbital ventricular puncture: review of the technique and report of a case: https://doi.org/10.59156/revista.v37i01.456 - Picard, Nelson; Gómez, Gisella E.; Zanardi, Carlos A. (Revista Argentina de Neurocirugía, 2023)
Transorbital ventricular puncture (TOP) is a fast and simple but poorly understood technique. As it can be performed at the patient’s bedside, it is ideal in patients with rapidly evolving acute hydrocephalus or with imminent or recent transtentorial herniation, in whom expeditious access to the ventricular cavities can be life-saving. We review the historical development of the technique since its original description in 1933. Finally we present the case of a patient with acute hydrocephalus secondary to cerebellar edema, in whom the use of TOP allowed time to implement definitive treatments. The technique used by us consisted of an entry point through the upper eyelid, behind the superior orbital rim, and at the midpupillary line, with a trajectory aimed towards the sagittal suture two to three finger widths behind the coronal suture.